Modernization of the register of land and buildings with reference to entering buildings into the real estate cadastre in Poland - Buśko, Małgorzata (International Conference “Environmental Engineering”, 2017)
Nowadays, it is frequently the case that the database of the real estate cadastre in Poland is not supplied with the record data on buildings. This study presents the issues related to the comprehensive modernization of the register of land and buildings, especially in the aspect of entering the buildings located in the areas of the modernized cadastral districts, into the database of the real estate cadastre. The real estate cadastre should provide a reference base for other public records, the data contained in the cadastre should be the basis, for example, for official statistics, real estate management and register of farms, or tax records. The analysis of this procedure was based on the data derived from the modernization of the register of land and buildings carried out in eleven cadastral units of Gorlice district, province of Malopolska, as part of the national project: Development of an Integrated Real Estate Information System – (ZSIN) – Stage I. In this project, the data for the preparation of the digital description of the contour of a building were captured largely based on high-precision aerial imagery which, having been developed on the stereoscopic model, supplied the digital database of the real estate cadastre. A serious problem, which hinders the maintenance of the database of the real estate cadastre in Poland updated, are the frequent amendments to the applicable laws. The Regulation on the register of land and buildings, according to which the cadastral database has been built in Poland since 2001, was extensively amended in 2013 and in 2015. This makes it difficult to obtain uniform data of the buildings in Poland.